A Case of Adenocarcinoma of Uterus Masculinus in a Pomeranian Dog - Vignoli, Massimo; De Amicis, Ippolito; Tamburro, Roberto; Quaglione, Gina; Salviato, Nicoletta; Collivignarelli, Francesco; Terragni, Rossella; Pastrolin, Stefano; Marruchella, Giuseppe (Frontiers in Veterinary Science, 2020)
Introduction - Persistent Müllerian duct syndrome (PMDS), or uterus masculinus, is a rare autosomal recessive form of male pseudohermaphroditism due to the failure of paracrine anti-Müllerian hormone (AMH) secretion by Sertoli cells or failure of the Müllerian ducts to respond to AMH secretion. The malignant degeneration of persistent Müllerian remnants is rare. In human medicine, few related reports exist. In veterinary medicine, this is the first report describing adenocarcinoma of the uterus masculinus involving the prostate in a dog. Clinical history - An 11-year-old, male, neutered Pomeranian dog was referred for computed tomography due to the suspicion of prostatic carcinoma based on ultrasound and cytological examinations. The computed tomography findings were consistent with a uterus masculinus mass with possible prostatic infiltration. Uterus masculinus removal and total prostatectomy were performed; termino-terminal urethral anastomosis was carried out. Dehiscence of the anastomosis was observed three days after surgery. The owner declined any further procedures, and the dog was euthanized five days after surgery. Histopathological evaluation revealed adenocarcinoma of the uterus masculinus. Conclusion - Adenocarcinoma of the uterus masculinus may occur, suggesting that patients with PMDS should be evaluated for malignant changes of Müllerian remnants.